2017
DOI: 10.12973/ejmste/81153
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Behaviours towards the Environmental Issues: Case of Northern Cyprus

Abstract: The study aims to investigate the knowledge of students as well as the relationship between attitudes and behaviour also based on gender towards the environmental issues. For this purpose, a survey study was conducted using a group of students who are the eighth grade students at a secondary school in the North Cyprus. This study was performed in the second half term in the 2016-2017 academic year. In the study, the research data was gathered with "Environmental Knowledge Test", "Environmental Attitude Scale" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 33 publications
5
13
0
2
Order By: Relevance
“…For the engagement in direct PEBs, environmental knowledge provided through a formal environmental education might not be strong enough to bring a positive change. This finding can be supported by the study of Varoglu et al [66], which reported a moderate relationship between environmental knowledge and environmental attitudes of students in secondary school level in North Cyprus and found a weak relationship between environmental knowledge and PEBs.…”
Section: Discussionsupporting
confidence: 67%
“…For the engagement in direct PEBs, environmental knowledge provided through a formal environmental education might not be strong enough to bring a positive change. This finding can be supported by the study of Varoglu et al [66], which reported a moderate relationship between environmental knowledge and environmental attitudes of students in secondary school level in North Cyprus and found a weak relationship between environmental knowledge and PEBs.…”
Section: Discussionsupporting
confidence: 67%
“…Varoglu et al [124] Environmental literacy, attitudes, awareness, and behaviour studies were conducted among 335 middle school students in Eskişehir to determine the effects of purchasing good environmental products. The study showed that environmental illiteracy has no major effect on the attitude and purchase of environmental products, while awareness has a positive effect on a pro-environmental attitude toward environmentally-friendly purchased products.…”
Section: Summary Of Objective and Findings Of Research Articlesmentioning
confidence: 99%
“…How these two variables showed significantly correlated with r = .693. Varoglu, Temel, & Yilmaz (2018) conducted studies on the relationship between knowledge, attitude, and behaviour of students. The findings show that environmental knowledge has a poor relationship but significant correlation (r = 0.21, p = 0.05) against environmental behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%